Simply synthesized silica hollow fibers for enhancing the performance of dye/quantum dot sensitized solar cells. (1st May 2019) - Sherafati-Tabarestani, Z.; Samadpour, M.
Graphical abstract: Highlights: A simple method is introduced for synthesizing silica hollow fibers. Silica hollow fibers are made with a scalable procedure. Silica hollow fibers show an effective light scattering properties. Efficiency of QDSCs is improved from 2.22% to 4.36% by utilizing silica fibers. Dark current is systematically decreased by utilizing nanofibers in QDSCs. Abstract: Silica nanofibers were fabricated by a novel and simple method for application in dye/quantum dot sensitized solar cells. Silica hollow fibers were made by dipping cotton fibers in a silica sol solution that was prepared according to the Stober method. Silica hollow fibers with micron lengths and nanostructured surface were obtained by removing the cotton fibers through thermal annealing. Silica nanofibers were utilized as a scattering layer in the photoanode structure of the dye/quantum dot sensitized solar cells. An effective scattering property of nanofibers was observed by diffuse reflectance spectroscopy. According to the obtained results, silica nanofibers have a clear effect on improving the current density and consequently efficiency of cells. The dark current was remarkably reduced by incorporating silica nanofibers in the photoanode structure of cells. Here 4.36% efficiency (Voc  = 624 mV, Jsc  = 13.72 mACm −2, FF = 0.51) was obtained by optimizing the percent of silica nanofibers in the photoanode structure. This is more than 120% efficiency enhancement in comparison to cells with only TiO2 photoanode structures with 1.95% efficiency.